Experimental Study of Imbibition Within Core Chips of Shale in Ordos Basin - Wu, Jiang; Mu, Lijun; Ren, Dazhong; Liu, Jin; Hui, Honggang; Wang, Zhenze (Frontiers in Physics, 2022)
The main exploring technology of No.7 Yanchang Formation of the Triassic reservoir in the basin adopts quasi-natural downhole energy driven by volume fracturing, and the region production thus cannot be improved by injection well network. The EOR has been carried out through enhanced imbibition process during the reservoir stimulation work. For further understanding the oil-water displacement mechanism in core scale, the tight sandstone thin cut chips imbibition experimental study was carried out. Simultaneously, application of nuclear magnetic resonance (NMR) to the pore fluid changes within chips were measured. This novel method provides another experimental way to study the imbibition mechanism of low permeability reservoir imbibition behavior. This method was used to evaluate the application effect of imbibition surfactant in use, and the field practice was compared and analyzed by means of chemical tracer among dozens of clusters in same horizontal well.